2002
DOI: 10.1016/s0886-3350(01)01258-5
|View full text |Cite
|
Sign up to set email alerts
|

Vector summation of anterior and posterior corneal topographical astigmatism

Abstract: Consideration of the Orbscan measurement of posterior corneal surface toricity may improve the prediction of the magnitude of refractive astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 26 publications
2
21
1
1
Order By: Relevance
“…[7][8][9][10] In these studies, total corneal astigmatism was calculated by vector summation of anterior and posterior corneal astigmatism, assuming parallel rays approaching the posterior corneal surface and ignoring the contribution of corneal thickness.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10] In these studies, total corneal astigmatism was calculated by vector summation of anterior and posterior corneal astigmatism, assuming parallel rays approaching the posterior corneal surface and ignoring the contribution of corneal thickness.…”
Section: Resultsmentioning
confidence: 99%
“…15 Since then, studies 16,17 have shown the benefit of using TCP, in particular in the estimation of the corneal power in IOL calculation after refractive surgery. Other studies 18,19 report good IOL power calculation outcomes using the TCP value from a dual Scheimpflug 20 found an improvement in the prediction of the refractive astigmatism when the posterior corneal surface measurement was added to the calculation. Ho et al 10 found an error in corneal astigmatism magnitude estimation of more than 0.50 D in 28.8% of eyes using the anterior corneal measurement only.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] These studies have found levels of astigmatism for the posterior cornea ranging from 0.18-0.31 D. The curvature of the posterior cornea combined with the refractive index difference between the cornea and the aqueous means that the posterior corneal astigmatism is of opposite sign to that of the anterior cornea. Therefore, the compensation of corneal astigmatism by the eye's internal optics can be attributed, in part, to the astigmatism of the posterior cornea.…”
Section: Corneal and Internal Astigmatismmentioning
confidence: 99%